International careers of researchers in biomedical sciences: a comparison of the US and the UK - Lawson, Cornelia; Geuna, Aldo; Kataishi, Rodrigo; Toselli, Manuel; Fernández-Zubieta, Ana (University of Sussex, 2015)
"This chapter analyses the mobility of academic biomedical researchers in the US and the UK. Both countries are at the forefront of research in biomedicine, and able to attract promising researchers from other countries as well as fostering mobility between the US and the UK. Using a database of 292 UK based academics and 327 US based academics covering the period 1956 to 2012, the descriptive analysis shows a high level of international mobility at education level (BA, PhD and Postdoc) with small, but significant transatlantic exchanges, and shows high levels of cross-border mobility amongst senior academics based in the UK. There is a high level of career mobility with 50% of the sample having changed jobs at least once, and 40% having moved within academia. There is no significant difference in job-job mobility between the two countries although there are some interesting institutional differences concerning international and cross-sector mobility. The empirical analysis focuses on the importance of postdoctoral training in the US and the UK. The results indicate that working in the US is correlated to higher researcher performance in terms of both publication numbers and impact/quality adjusted publications (in top journals and average impact). The publications of researchers with postdoctoral experience are generally of a higher average impact. This applies especially to postdoc experience at top-quality US institutions although a postdoc at a UK top institution is associated with higher top journal publications and higher average impact. In relation to the UK sample, we find that a US postdoc (especially in a top institution) is correlated to subsequent performance in the UK academic market. Finally, we see that US postdocs that stay in the US publish more and publications with higher impact/quality than those that move to the UK; however, these effects are stronger for those who studied for their PhD degree outside the US. Therefore, we find some evidence that the US is able to retain high performing incoming PhD graduates."